2017
DOI: 10.1007/s10096-017-3073-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and trends in the antimicrobial susceptibility pattern of Salmonella enterica serovars Typhi and Paratyphi A among children in a pediatric tertiary care hospital in South India over a period of ten years: a retrospective study

Abstract: The aim of this study was to determine the prevalence and trends in the antimicrobial resistance of typhoidal salmonellae in children and adolescents at a pediatric tertiary care hospital in South India. Typhoidal salmonellae were isolated from 483 of the 77,713 blood cultures received during the ten-year study period (2007-2016). Isolates were speciated by conventional biochemical reactions and serotyping. Antimicrobial susceptibility testing was performed and interpreted according to the British Society for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 20 publications
6
28
1
Order By: Relevance
“…The decline in the ACCo resistance could be attributed to limited use of these antibiotics due to the availability of better alternatives like 3rd generation cephalosporins. On the other hand, there has been an increasing trend of resistance to quinolones in Salmonella and now almost 90-100% quinolone resistance in S. typhi & Paratyphi A has been reported especially after British Society of Antimicrobial & Chemotherapy (BSAC) revised its breakpoint guidelines in the year 2011 [20]. At authors' center, they have also observed a high resistance to quinolones (96%) and nil resistance to ceftriaxone in the pediatric population during the years 2014-2018.…”
Section: Etiology Of Bsi/blood Culture Isolatesmentioning
confidence: 95%
See 3 more Smart Citations
“…The decline in the ACCo resistance could be attributed to limited use of these antibiotics due to the availability of better alternatives like 3rd generation cephalosporins. On the other hand, there has been an increasing trend of resistance to quinolones in Salmonella and now almost 90-100% quinolone resistance in S. typhi & Paratyphi A has been reported especially after British Society of Antimicrobial & Chemotherapy (BSAC) revised its breakpoint guidelines in the year 2011 [20]. At authors' center, they have also observed a high resistance to quinolones (96%) and nil resistance to ceftriaxone in the pediatric population during the years 2014-2018.…”
Section: Etiology Of Bsi/blood Culture Isolatesmentioning
confidence: 95%
“…In a study by Iyer et al, the prevalence of enteric fever at a pediatric tertiary care hospital from South India during the tenyear study period from 2007 to 2016, was found to be 0.5% and 0.1% for S. typhi and S. paratyphi A, respectively [20]. On the other hand, in a systematic review and meta-analysis in adults and children in India, a prevalence of 9.7% of S. typhi and 0.9% of S. paratyphi A was observed [21].…”
Section: Etiology Of Bsi/blood Culture Isolatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ciprofloxacin (cip) resistance first emerged in the early 1990s. At present, over 90% of clinical isolates from regions of endemicity show reduced susceptibility to ciprofloxacin ( 6 , 7 , 11 ). These events shifted the first-line and empirical treatments to other classes of antimicrobial agents, such as ceftriaxone (cro) and azithromycin.…”
Section: Introductionmentioning
confidence: 99%